Identification of gene markers for the prediction of allograft rejection or permanent acceptance. - Sawitzki, B; Bushell, A; Steger, U; Jones, N; Risch, K; Siepert, A; Lehmann, M; Schmitt-Knosalla, I; Vogt, K; Gebuhr, I; Wood, K; Volk, H (2007)
The clinical success of new treatment strategies aiming on inducing permanent graft acceptance will rely on the ability to determine whether specific unresponsiveness to donor alloantigens has developed and for how long it is maintained. To identify markers for such posttransplant monitoring, genes differentially expressed by graft infiltrating leukocytes during tolerance induction or rejection after kidney transplantation in rats were compared. A subsequently performed full kinetic analysis in two different transplant models, kidney and heart, in two species, rat and mouse identified two markers (TOAG-1, alpha-1,2-mannosidase) with high specificity and reproducibility, which are highly expressed during induction and maintenance of acceptance, and downregulated during rejection. Expression level of these markers showed a strong positive correlation with graft function. In addition, expression of both genes was downregulated in the peripheral blood and the graft prior to rejection, suggesting that these markers may be useful for monitoring in clinical transplantation where peripheral blood is the most easily accessible patient sample. Interestingly, downregulation of TOAG-1 and alpha-1,2-mannosidase expression occurred in graft infiltrating cells and expression of both genes was also downregulated after T-cell activation in vitro.